A 1, 2, 3-triazolyl based conjugated microporous polymer for sensitive detection of p-nitroaniline and Au nanoparticle immobilization. Issue 27 (27th June 2018) - Wei, Feng; Cai, Xinyi; Nie, Junqi; Wang, Feiyi; Lu, Cuifen; Yang, Guichun; Chen, Zuxing; Ma, Chao; Zhang, Yuexing
Abstract : A 1, 2, 3-triazolyl based fluorescent CMP was used as an excellent chemosensor for p -nitroaniline detection and a support for Au catalyst deposition. Abstract : A 1, 2, 3-triazolyl based fluorescent conjugated microporous polymer PTPTB was synthesized through FeCl3 promoted oxidative coupling of 1, 3, 5-tris(1-(3, 5-di(thiophen-2-yl)phenyl)-1 H -1, 2, 3-triazol-4-yl)benzene. The resulting product has a BET surface area of 808.6 m 2 g −1 and exhibits a strong emissive peak centered at 525 nm upon excitation at 417 nm in DMF. As a chemical sensor, PTPTB showed good fluorescence sensing ability for p -nitroaniline ( p -NA) with a K sv of 7.08 × 10 4 M −1 and a detection limit of 4.2 × 10 −6 M. The electron-rich polymer was further employed to load Au nanoparticles (NPs). The formed Au/PTPTB composite showed superior catalytic activity in the catalytic reduction of p -nitrophenol ( p -NP) to p -aminophenol ( p -AP) and the rate constant was obtained to be 0.812 min −1 . Moreover, the catalyst can be readily recovered and reused for six runs without obvious loss of its activity.